Droplet‐based microfluidics systems in biomedical applications. Issue 11 (4th April 2019) - Feng, Huanhuan; Zheng, Tingting; Li, Mingyu; Wu, Junwei; Ji, Hongjun; Zhang, Jiaheng; Zhao, Weiwei; Guo, Jinhong
Abstract: Microfluidics has made a very impressive progress in the past decades due to its unique and instinctive advantages. Droplet‐based microfluidic systems show excellent compatibility with many chemical and biological reagents and are capable of performing variety of operations that can implement microreactor, complex multiple core–shell structure, and many applications in biomedical research such as drug encapsulation, targeted drug delivery systems, and multifunctionalization on carriers. Droplet‐based systems have been directly used to synthesize particles and encapsulate many biological entities for biomedicine applications due to their powerful encapsulation capability and facile versatility. In this paper, we review its origin, deviation, and evolution to draw a clear future, especially for droplet‐based biomedical applications. This paper will focus on droplet generation, variations and complication as starter, and logistically lead to the numerous typical applications in biomedical research. Finally, we will summarize both its challenge and future prospects relevant to its droplet‐based biomedical applications.